2010
DOI: 10.1007/s00441-010-0959-7
|View full text |Cite
|
Sign up to set email alerts
|

Smooth-muscle-specific expression of neurotrophin-3 in mouse embryonic and neonatal gastrointestinal tract

Abstract: Vagal gastrointestinal (GI) afferents are essential for the regulation of eating, body weight, and digestion. However, their functional organization and the way that this develops are poorly understood. Neurotrophin-3 (NT-3) is crucial for the survival of vagal sensory neurons and is expressed in the developing GI tract, possibly contributing to their survival and to other aspects of vagal afferent development. The identification of the functions of this peripheral NT-3 thus requires a detailed understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 113 publications
1
14
0
Order By: Relevance
“…β-galactosidase staining was also observed in the intestinal mucosa at E17 (Figure 1D,E). This staining may have reflected the presence of endogenous β-galactosidase as previously described at E17 and postnatal day 4 (Fox and McAdams, 2010), although some likely represents recombination as it occurred in these tissues at younger ages, prior to the appearance of endogenous enzyme (e.g., stomach epithelium; Figure 1A). Importantly, no β-galactosidase expression was detected in brain parenchyma at any of the embryonic ages examined, whereas it was present in a small number of adult brain regions by 2 months of age (illustrated for offspring of SM22α cre mice and BDNF lox reporter mice; see below).…”
Section: Resultsmentioning
confidence: 56%
“…β-galactosidase staining was also observed in the intestinal mucosa at E17 (Figure 1D,E). This staining may have reflected the presence of endogenous β-galactosidase as previously described at E17 and postnatal day 4 (Fox and McAdams, 2010), although some likely represents recombination as it occurred in these tissues at younger ages, prior to the appearance of endogenous enzyme (e.g., stomach epithelium; Figure 1A). Importantly, no β-galactosidase expression was detected in brain parenchyma at any of the embryonic ages examined, whereas it was present in a small number of adult brain regions by 2 months of age (illustrated for offspring of SM22α cre mice and BDNF lox reporter mice; see below).…”
Section: Resultsmentioning
confidence: 56%
“…Hence, although NT-3 mRNA and protein levels increased in the submandibular gland during chronic stress, this did not seem to significantly contribute to the increased plasma NT-3 levels. Expression of NT-3 has been investigated in several other organs, including heart, lung, liver, pancreas, and stomach,33,38-41 however, there have been no previous reports that examined the mechanism by which NT-3 increases under stress conditions. Several studies have shown that increased levels of monoaminergic neurotransmitters, including adrenaline, noradrenaline, serotonin, and dopamine, induce BDNF expression in the brain under stress conditions 42-44.…”
Section: Discussionmentioning
confidence: 99%
“…First, expression of Cre recombinase in SM22α cre mice is largely restricted to smooth muscle, the main GI tissue that expresses NT-3 (33, 34, 36, 57). Second, tests with a Cre-dependent reporter strain provided evidence of high recombination efficiency in smooth muscle (34, 57).…”
Section: Methodsmentioning
confidence: 99%
“…NT-3 expression in the majority of developing GI organs is largely restricted to smooth muscle cells comprising the outer layers of the developing stomach, cecum, small and large intestines, and the walls of blood vessels that supply the GI tract (33, 36). However, each organ exhibits a unique expression pattern.…”
mentioning
confidence: 99%